2017
DOI: 10.1002/jcb.26255
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes of Wistar and Sprague Dawley rats differ significantly in their central metabolism

Abstract: Wistar and Sprague-Dawley (SD) rats are most commonly used experimental rats. They have similar genetic background and are therefore, not discriminated in practical research. In this study, we compared metabolic profiles of Wistar and SD rat hepatocytes from middle (6 months) and old (23 months) age groups.Principle component analysis (PCA) on the specific uptake and production rates of amino acids, glucose, lactate and urea indicated clear differences between Wistar and SD rat hepatocytes. SD rat hepatocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Higher baseline corticosterone levels have also been reported in Wistar rats compared to Sprague Dawley [48], possibly affecting both fructose-induced hepatic gluconeogenesis [49] and affective behavior via HPA axis activation [24,50]. Cultured hepatocytes from Sprague Dawley rats also exhibit faster glucose and amino acid metabolism than in Wistar rats [51], suggesting Sprague Dawley and Wistar rats may metabolize fructose in the liver at different rates.…”
Section: Genetic Strain Differences Could Affect Response To Dietary mentioning
confidence: 98%
“…Higher baseline corticosterone levels have also been reported in Wistar rats compared to Sprague Dawley [48], possibly affecting both fructose-induced hepatic gluconeogenesis [49] and affective behavior via HPA axis activation [24,50]. Cultured hepatocytes from Sprague Dawley rats also exhibit faster glucose and amino acid metabolism than in Wistar rats [51], suggesting Sprague Dawley and Wistar rats may metabolize fructose in the liver at different rates.…”
Section: Genetic Strain Differences Could Affect Response To Dietary mentioning
confidence: 98%
“…The giant femur measured 6.15 mm in M-L and 4.87 mm in C-C midshaft diameter, whereas the smaller rat's femur midshaft was 2.33 and 1.98 mm wide in the M-L and C-C aspects, respectively. By extension, the giant femoral size is likely to have been associated with a larger body mass and skeletal frame (Damuth et al, 1990), well above a typical 150-300 g weight reported for common rats (e.g., Bromage et al, 2009;Felder et al, 2017;Garg et al, 2018). At the histological level, both samples exhibited circumferential bone periosteally and endosteally, and multiple osteocyte lacunae scattered throughout the entirety of bone (Figs.…”
Section: Resultsmentioning
confidence: 86%
“…One of the possible mechanisms related to increased blood lipids is the olanzapine‐enhanced expression of steroid regulatory element‐binding protein (SREBP)‐1c expression, for which transcription in adipose tissue and liver depends on insulin 39 . Despite hepatic‐related metabolic abnormalities models being reproducible in Wistar and Sprague Dawley lineages, 43,44 antipsychotic changes in carbohydrates and lipids metabolism should be carefully interpreted due to differences in hepatic amino acid uptake and glycolytic cycle among species and even in rat strains 45 . Thus, the use of the Wistar strain limits comparisons with other data in the literature, constituting a limitation of this work, but it brings important information about the metabolic effects of olanzapine and clozapine.…”
Section: Discussionmentioning
confidence: 99%